Synthesis, spectral characterization and antimicrobial activity of some M(II) complexes with Ciprofloxacin - Emir Horozić; Amira Cipurković; Zahida Ademović; Demir Bjelošević; Amila Zukić; Lamija Kolarević; Darja Husejnagić; Snježana Hodžić (Journal of Engineering & Processing Management, 2018)
Ciprofloxacin, CFL is a drug that belongs to the second generation of fluoroquinolone antibiotics with a wide range of effects on Gram-positive and Gram-negative bacteria. The aim of this work was to investigate the interaction of CFL as ligand with divalent biological cations (Mn2+, Ni2+ and Co2+) in approximate physiological conditions. Synthesized complexes were characterized using FTIR and stereo-microscopy. Antimicrobial screening was performed on bacterial strains of Escherichia coli, Salmonella Enteritidis, Enterococcus faecalis and Staphylococcus aureus. The results of FTIR spectroscopy showed that the M(II) complexes with CFL were formed through the oxygen donors of the carboxyl and carbonyl group of the ligand. Stereo-microscopic characterization revealed the difference in color and size of crystals of the ligand and metal complexes. Antimicrobial screening has shown that CFL and complexes have almost similar antimicrobial activity against investigated bacterial strains.
Keywords: complex; CPF; antimicrobial activity; morphological characterization; FTIR